Begin again - Carney, John, 1972-; Corden, James; Knightley, Keira, 1985-; Ruffalo, Mark ([Place of publication not identified] : [publisher not identified], 2014)
When a young female singer moves to New York City in hopes of breaking into show business, she falls for an executive at a record company who helps her in her endeavors.
Anamorphic wide screen 1.78:1.
James Corden, Keira Knightley, Mark Ruffalo, Hailee Steinfeld, Mos Def.
MPAA rating: R.
Keywords: Man-woman relationships -- Drama; Women singers -- Drama; Sound recording executives and producers -- Drama; Romantic comedy films; Romance films; Musical films; Fiction films; Feature films; Comedy films